Resistance of Listeria monocytogenes to Stress Conditions Encountered in Food and Food Processing Environments - Bucur, Florentina Ionela; Grigore-Gurgu, Leontina; Crauwels, Peter; Riedel, Christian U.; Nicolau, Anca Ioana (Frontiers in Microbiology, 2018)
Listeria monocytogenes is a human food-borne facultative intracellular pathogen that is resistant to a wide range of stress conditions. As a consequence, L. monocytogenes is extremely difficult to control along the entire food chain from production to storage and consumption. Frequent and recent outbreaks of L. monocytogenes infections illustrate that current measures of decontamination and preservation are suboptimal to control L. monocytogenes in food. In order to develop efficient measures to prevent contamination during processing and control growth during storage of food it is crucial to understand the mechanisms utilized by L. monocytogenes to tolerate the stress conditions in food matrices and food processing environments. Food-related stress conditions encountered by L. monocytogenes along the food chain are acidity, oxidative and osmotic stress, low or high temperatures, presence of bacteriocins and other preserving additives, and stresses as a consequence of applying alternative decontamination and preservation technologies such high hydrostatic pressure, pulsed and continuous UV light, pulsed electric fields. This review is aimed at providing a summary of the current knowledge on the response of L. monocytogenes towards these stresses and the mechanisms of stress resistance employed by this important food-borne bacterium. Circumstances when L. monocytogenes cells become more sensitive or more resistant are mentioned and existence of a cross-resistance when multiple stresses are present is pointed out.